The Bazaar Economy: Information and Search in Peasant Marketing - Clifford J. Geertz (Journal of Economic Sociology, 2010)
This paper describes major principles governing the organization of bazaar. The bazaar economy shows a number of distinctive characteristics that distinguish it from the perfect market as well as non-market economy. The search for information and its protection are central treats of life in the bazaar. Search efﬁ ciency depends on two most important procedures, namely: clientelization and bargaining. The bazaar does not correspond to a stereotypical vision describing it as a chaotic crowd phenomenon. Instead, it presents a complex structure of ties among participants involved in close relations of competition and interdependency